PENINGKATAN KEMAMPUAN BERPIKIR KRITIS DENGAN MENGGUNAKAN PENDEKATAN OPEN ENDED PADA MATA PELAJARAN MATEMATIKA DIKELAS IV SD - Puput Wahyu Hidayat; Andam Yulianti; Anthoni S (LP3M STKIP Muhammadiyah Muara Bungo, 2019)
The problem in this study is the learning process and the critical thinking skills of students in mathematics learning in Class IV SD Negeri 176/II Renah Sungai Ipuh is still low, this is evidenced by the results of preliminary observations made by researchers from 33 students only 9.09% those who score in criteria are quite critical. The reason is that the teacher only uses a conventional approach in the classroom, which causes the learning process and students' critical thinking skills to be low. The purpose of this study was to describe the application of an open ended approach to the learning process of students and students' critical thinking abilities. The method used in this study is classroom action research (CAR). This study consisted of 2 cycles, each cycle carried out through 4 stages, namely planning, action, observation and reflection and consisted of 2 meetings. The results of the study can be explained as follows: (1) the application of the open ended approach in the learning process is seen from the obervation sheet that the first cycle is only from the aspect of the teacher 66,25% and the aspect of the students 64,7% while in the second cycle there is an increase from the teacher aspect 83,75% and the aspect of the students 85,97% who have achieved an indicator of success. (2) the application of the open ended approach in learning in the first cycle is still not maximal. This can be seen from the results of the tests in the first cycle, only 27,27% of the students who received the criteria were quite critical and 72,72% of the students had not yet achieved the indicators of success. students' critical thinking skills improve very well in cycle II. From 9.09% (initial observation), it becomes 27,27% (cycle I) and 57,57% (cycle II).